2014
DOI: 10.1186/1748-5908-9-84
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon’s experiences of receiving peer benchmarked feedback using patient-reported outcome measures: a qualitative study

Abstract: BackgroundThe use of patient-reported outcome measures (PROMs) to provide healthcare professionals with peer benchmarked feedback is growing. However, there is little evidence on the opinions of professionals on the value of this information in practice. The purpose of this research is to explore surgeon’s experiences of receiving peer benchmarked PROMs feedback and to examine whether this information led to changes in their practice.MethodsThis qualitative research employed a Framework approach. Semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(89 citation statements)
references
References 42 publications
1
88
0
Order By: Relevance
“…In our review, we found that clinicians remained sceptical about the validity of PROMs data for a number of reasons, including their reliance on patients' subjective reports and the process of case-mix adjustment. 97,194 GPs were also not convinced that patient experience data reflected what they considered to be 'good care.' 223 Indeed, recent evidence indicates that following good practice in terms of antibiotics prescribing may reduce patient satisfaction.…”
Section: Credibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In our review, we found that clinicians remained sceptical about the validity of PROMs data for a number of reasons, including their reliance on patients' subjective reports and the process of case-mix adjustment. 97,194 GPs were also not convinced that patient experience data reflected what they considered to be 'good care.' 223 Indeed, recent evidence indicates that following good practice in terms of antibiotics prescribing may reduce patient satisfaction.…”
Section: Credibilitymentioning
confidence: 99%
“…However, providers may question if the subjective reports of patients can serve as reliable indicators of their health outcomes, and some have expressed concerns that patients' ratings of their outcomes may be unduly influenced by their experiences. 97,194,223 The underlying assumption of all of these claims is that it is the data and what is done to the data (i.e. case-mix adjustment) that providers object to.…”
Section: Feedback Of Proms: Reviewing Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other literature is focussed mainly on preferences of patients or clinicians, but this study includes preferences of four different stakeholders. 22,36,37 It is also directed towards different types of indicators, namely process, structure and outcome indicators. Furthermore, it…”
Section: Discussionmentioning
confidence: 99%
“…However, audit and feedback tools can only be effective if physicians access them to review their clinical performance data. Physicians who do not see their performance feedback data are not likely to use it for quality improvement [2]. Thus, there is a need to understand how to promote access to, and ultimately use of, audit and feedback tools among physicians.…”
Section: Introductionmentioning
confidence: 99%